PENGEMBANGAN FILM DOKUMENTER BERBASIS AUDIO VISUAL SEBAGAI MEDIA PEMBELAJARAN PADA MATERI PENCEMARAN LINGKUNGAN - Sofiyah, Siti; Hadi, Wiwin Puspita; Qomaria, Nur; Fikriyah, Aida; Rakhmawan, Aditya (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
Documentary film is a film based on true events. The purpose of this study was to determine the feasibility and response of students to documentary films. This research is a development research using the ADDIE model. The results of the material validation results obtained a score of 90% anda reliability of 92,6%. Media validation results obtained a score of 96% and 98% reliabilty. Based on the validation results, it is known that documentary films are suitable for use. While the results of the average lift the response of students get a score 80,38% (good) so that it can be concluded that students are interested in learning environmental pollution materials using documentaries.